2013
DOI: 10.2131/jts.38.49
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar concentration of triclocarban increases the vulnerability of rat thymocytes to oxidative stress

Abstract: -It was recently reported that triclocarban was absorbed significantly from soap used during showering in human subjects and that its C max in their whole blood ranged from 23 nM to 530 nM. We revealed that a nanomolar concentration (300 nM) of triclocarban potentiated the cytotoxicity of 300 μM H 2 O 2 in rat thymocytes by using cytometric techniques with appropriate fluorescent probes. Although 300 nM triclocarban did not itself increase the population of dead cells (cell lethality), it facilitated the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…These processes were accompanied by ROS formation, LDH release, and neuronal cell death. Our results are in accordance with cytotoxic effect of triclocarban used in combination with hydrogen peroxide in rat thymocytes [ 8 ]. The results are also in line with the lethality of rat pups that were fed by lactating females exposed to triclocarban [ 6 ].…”
Section: Discussionsupporting
confidence: 89%
“…These processes were accompanied by ROS formation, LDH release, and neuronal cell death. Our results are in accordance with cytotoxic effect of triclocarban used in combination with hydrogen peroxide in rat thymocytes [ 8 ]. The results are also in line with the lethality of rat pups that were fed by lactating females exposed to triclocarban [ 6 ].…”
Section: Discussionsupporting
confidence: 89%
“…Both human cell lines (T47Dluc, H295R) showed no cell lethality when exposed up to 1.6 μM TCC. These results are in agreement with the open literature [128,129]. …”
Section: Discussionsupporting
confidence: 94%
“…Morita et al [126] showed no cell lethality after the incubation of rat thymocytes with TCC at concentrations ranging from 30 to 500 nM for 1 h. The incubation with TCC at concentrations ranging from 10 to 1 μM for 1 h did not affect the viability of rat thymocytes [128]. Another study by Kanbara et al [129] showed an increase in cell lethality when rat thymocytes were incubated with 10 μM TCC. In the present study, a cytotoxic effect to treated RTL-W1 cells was already observed at concentrations above 4 μM TCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation